Neoliberalism and HIV/AIDS prevention in Brazil - Cristiano, Gabriela Dutra (Argumentum, 2024)
This article analyses the concepts underlying HIV/AIDS prevention policy in Brazil in the context of neoliberalism. It is documentary research in which six national documents that guide the management and execution of the policy were submitted to discursive textual analysis (Moraes, 2003), revealing its foundations and priority strategies. It concludes that the notions of combination, autonomy, freedom and the possibility of making choices are the main concepts that underlie the policy. Their inclusion is not neutral and, in the way they appear, they are consistent with neoliberal rationality, they incorporate business logic, and make the assumption that the simple desire of individuals to want to prevent infection makes it possible for them to make choices from a menu of prevention strategies, without measuring of the way alternatives are placed in reality.